Family functioning and resilience in patients with noncommunicable diseases of a public hospital in Metropolitan Lima - Moises Céspedes Felix (2019)
Objective: of the present investigation was to: study the relationship between family functioning andresilience variables in patients with noncommunicable diseases of a public hospital in Lima. Materialand Methods: of the research was non-experimental, cross-sectional and correlational in scope. Themodel of family functioning on which we worked was the Circumplex family system model by Olson,Russell and Sprenkle (1979). The scale used to measure family functioning was the Family Cohesionand Adaptability Assessment Scale (FACES III) and to measure resilience, the Resilience Scaledeveloped by Wagnild and Young (1993) was used, which consists of five dimensions. The sampleconsisted of 109 patients. In the Results it was found that family functioning is not related to resilience(x2 = 5.972, p> .05). Therefore, it is Conclussion: that whatever the level of family functioning, it ispossible that the patient is resilient; since there are individual factors that intervene in the developmentof resilience.